Effects of Sodic Soil Reclamation using Flue Gas Desulphurization Gypsum on Soil Pore Characteristics, Bulk Density, and Saturated Hydraulic Conductivity. Issue 4 (14th July 2014) - Yu, Haoliang; Yang, Peiling; Lin, Henry; Ren, Shumei; He, Xin
Abstract : Soil pore structure is critical to water, air, and solute movement in soils. Sodic soil reclamation using flue gas desulphurization (FGD) gypsum is expected to improve soil physical characteristics. However, quantification of complex pore structural changes during the reclamation process, as well as their relationships to sodic soil properties, remains elusive. The objectives of this study were to evaluate the impact of different sodic soil reclamation methods using FGD gypsum on soil pore parameters based on computed tomography (CT) and to identify quantitative relationships between sodic soils pore parameters and saturated hydraulic conductivity ( K sat ). A field experiment with nine different treatments (three levels of FGD gypsum amount × three levels of leaching water) was conducted in the Hetao irrigation district in northern China. Undisturbed soil cores (40 mm diameter by 9 mm height) were collected with two replicates from four depths (0–10, 10–20, 20–40, and 40–60 cm) in each treatment after 2 yr. Two images were acquired from two specific positions in each soil core using a micro‐CT with 0.034 by 0.034 mm pixel resolution, and the images were quantified for various soil pore parameters. Soil dry bulk density and K sat were also measured using intact soil cores collected in situ. The results indicated that the reclamation treatments with both FGD gypsum and leaching water increased soil porosity >0.034 mm, macroporosity, mesoporosity, elongated porosity, irregular porosity, regular porosity, and K sat, and decreased bulk density in the 0‐ to 20‐cm depth. However, the treatment with high level of leaching water had no positive influence on pore space at the 20‐ to 40‐cm depth. Treatments with either FGD gypsum or leaching water alone only positively influenced pore structure at the 10‐ to 40‐ and 0‐ to 10‐cm depths, respectively. Macroporosity plus bulk density explained most of the variability in K sat ( R 2 = 0.77). This study illustrates the benefits of applying FGD gypsum and leaching water for improving pore structure critical for sodic soil water flow and suggests that a balanced amount of FGD gypsum and leaching water based on pore structure improvement is needed for achieving optimal sodic soil reclamation outcome.